Pengetahuan tenaga kesehatan tentang tuberkulosis paru dan diabetes melitus di Puskesmas Kota Manado - Sugeha, Bonita; Palandeng, Henry M. F.; Ottay, Ronald I. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2017)
Tuberculosis is a disease caused by infection with mycobacterium tuberculosis. Across the world there were an estimated 9.6 million people have been exposed to tuberculosis in 2014. Diabetes mellitus is a group of metabolic diseases with characteristic hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action, or both. World Health Organization (WHO) reported in 2011 there were 8% of the population worldwide suffer from diabetes mellitus and predicted increase of about 10% in 2030. This study aims to determine the health worker knowledge about pulmonary tuberculosis and diabetes mellitus. This research is a qualitative descriptive design with cross sectional studies. The data collection was done by using in-depth interviews with a sample of 10 health workers using purposive sampling method. The results of this study indicate that in general the informants have been able to answer correctly about pulmonary tuberculosis and diabetes mellitus, but there are several answers especially regarding review risk factors of pulmonary tuberculosis and diabetes mellitus are still not answered correctly, it is recommended that health workers can increasing knowledge by following the training and be more active in seeking information, especially with regard to pulmonary tuberculosis disease and diabetes mellitus.Keywords: knowledge, health workers, pulmonary tuberculosis, diabetes mellitus